Contending issues in South Africa's foreign policy : universalism versus economic national interest : the case of South Africa's arms sales to 'pariah states' 1994-1999 - Othieno, Timothy (Rhodes University, Faculty of Humanities, Department of Political and International Studies, 2005)
This study examines post-apartheid South African foreign policy under former President Nelson Mandela, and the apparent ambiguities that were its recurrent feature in the period from 1994 to 1999. Its focus is on the inherent irreconcilability of the economic national interests and the foreign policy principles which included the promotion of and respect for universalist principles and interests such as human rights, democracy, international peace and security. In examining South African foreign policy during this period, it would appear that the country was trapped between two competing priorities: the need to promote "universalist" principles and the need to satisfy its national economic interests. The main aim of the study is to explain how this "irreconcilability" between universalist principles and national economic interests would later create ambiguities and contradictions in South Africa's foreign policy, weaken respect for its foreign policy principles, and ultimately lead to ideological failure among politicians who employed 'short-term gain' policy decision-making in dealing with 'pariah states'. The study further demonstrates that "realist" national interests are frequently short-term, realizable and vital for a country, while universalist interests are long-term, idealistic and usually not easily realizable. It will be argued, therefore, that a country faced with making decisions about its vital national interests, will not make efforts to pursue long-term universalist interests if that choice would in any way endanger its fundamental national interests. In order to better assess this ambiguity, this thesis will provide a case study of Pretoria's arms sales to 'pariah states' during the period. The purpose of this study is not to attempt to explain all of the issues around post-apartheid foreign policymaking, or even to argue whether the sale of arms to 'pariah states' was 'politically incorrect', but to provide a 'piece of the puzzle' which might explain how the social and economic situation may have compelled Pretoria to sell arms when these actions disregarded universalist principles of foreign policy. The conclusion seems to confirm the realist view that universal values and principles can be regarded only when they are in harmony with a state's perceived self-interests.
Keywords: South Africa -- Foreign relations -- 1994-; South Africa -- Politics and government -- 1994; South Africa -- Foreign economic relations; Arms transfers -- South Africa